2013
DOI: 10.1039/c3sc50896j
|View full text |Cite
|
Sign up to set email alerts
|

A dinuclear silver hydride and an umpolung reaction of CO2

Abstract: A dinuclear silver hydride and an umpolung reaction of CO 2A silver lining: An N-heterocyclic carbene ligand supports a robust hydride-bridged disilver cation, with a silver-silver distance shorter than that in silver metal. Proton and silver NMR studies refl ect strong H-Ag and Ag-Ag dipolar coupling. The cation reacts very slowly with free CO 2 , but transfers hydride rapidly to CO 2 activated by a suitable Lewis base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 108 publications
7
49
1
Order By: Relevance
“…[178] The core of these complexes adopt a triangular structure, with a silverÀsilver distance shorter than that of silver metal. [178] The core of these complexes adopt a triangular structure, with a silverÀsilver distance shorter than that of silver metal.…”
Section: Scheme 14mentioning
confidence: 99%
“…[178] The core of these complexes adopt a triangular structure, with a silverÀsilver distance shorter than that of silver metal. [178] The core of these complexes adopt a triangular structure, with a silverÀsilver distance shorter than that of silver metal.…”
Section: Scheme 14mentioning
confidence: 99%
“…Silver hydrides are key intermediates in a number of reactions involving organic substrates5 and several silver hydrides have been recently isolated and structurally characterised by X‐ray crystallography 6. In one such study, hydrogen evolution from [(LAg) 2 H] + (where L=N‐heterocyclic carbene ligand 1,3‐bis(2,6‐diisopropylphenyl)imidazolin‐2‐ylidene) was observed, but the precise mechanism for H 2 formation is unknown 6e. Gas‐phase studies on mass selected silver hydride clusters allow their structure7 and reactivity8 to be directly probed.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] There is,h owever, ag rowing appreciation that species possessing three-center,two-electron M À H À Mb onds may play ar ole in catalysis.F or example,L alic and coworkers have shown that cationic dinuclear copper(I) hydride complexes are key catalytic intermediates in the hydroalkoxylation of alkynes. [12,13] Despite detailed studies on the preparation and reactivity of symmetric dinuclear coinage metal hydrides,little is known about heterobimetallic compounds with asymmetric MÀHÀ M' moieties.C ombinations of copper and gold NHC complexes catalyze the addition of phenols to internal alkynes with activities that are greater than the individual components of the mixture. [12,13] Despite detailed studies on the preparation and reactivity of symmetric dinuclear coinage metal hydrides,little is known about heterobimetallic compounds with asymmetric MÀHÀ M' moieties.C ombinations of copper and gold NHC complexes catalyze the addition of phenols to internal alkynes with activities that are greater than the individual components of the mixture.…”
mentioning
confidence: 99%